Family and peers : linking two social worlds - Kerns, Kathryn A., 1961-; Grau, Josefina M., 1960-; Neal-Barnett, Angela M., 1960- (Praeger series in applied psychology., 2000)
Why is it that relationships with family members predict the quality of children's relationships outside the family? This volume discusses, from a variety of critical perspectives, several mechanisms that may account for continuities across family and peer relationships.